Preparation method of epoxy and DCP (dicumyl peroxide) double-crosslinked EAA (ethylene acrylic acid) and LDPE (low-density polyethylene) cable material

By using biphenyl small molecule epoxy compound and DCP as dual crosslinking agents in high-voltage DC cable materials, the epoxy/EAA dual crosslinking system is solved, and the insulation characteristics of cable materials are damaged after breakdown are significantly improved, and the amount of crosslinking agent is reduced.

CN119684642AActive Publication Date: 2025-03-25HARBIN UNIV OF SCI & TECH

Patent Information

Application Number
CN202411557525.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-02
Publication Date
2025-03-25
Estimated Expiration
2044-11-02

AI Technical Summary

Technical Problem

The insulation characteristics of existing high-voltage DC cable materials are permanently damaged after breakdown, making it difficult to effectively improve the DC breakdown characteristics.

Method used

Biphenyl small molecule epoxy compounds and DCP as dual crosslinking agents were used to construct XLPE and epoxy/EAA dual crosslinking systems, and functional groups such as benzene ring and carbonyl are introduced through small molecule epoxy compounds to enhance the DC breakdown characteristics of cable materials.

Benefits of technology

It significantly improves the DC breakdown characteristics of cable materials, reduces the amount of crosslinking agent DCP, prevents scorching and over-crosslinking, and improves electric field distortion and electrical resistance characteristics without adding additional additives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005116934780000011
    Figure HDA0005116934780000011
  • Figure HDA0005116934780000012
    Figure HDA0005116934780000012
  • Figure HDA0005116934780000021
    Figure HDA0005116934780000021
Patent Text Reader

Abstract

The invention relates to a preparation method of an epoxy and DCP bi-crosslinked EAA and LDPE cable material, and belongs to the technical field of preparation of high-voltage direct-current cable materials. The preparation method of the cable material comprises the following steps: taking an ethylene acrylic acid copolymer EAA and low-density polyethylene LDPE as matrix resin, taking a biphenyl type micromolecular epoxy compound 4, 4 '-biphenol diglycidyl ether and dicumyl peroxide DCP as double crosslinking agents, and carrying out cross-linking reaction to prepare the cable material. And heating and pressurizing in a press vulcanizer to obtain the biphenyl micromolecular epoxy and DCP bi-crosslinked EAA / LDPE high-voltage direct-current cable material. A bi-crosslinking structure formed by biphenyl type micromolecule epoxy and DCP bi-crosslinking EAA / LDPE material and an in-situ introduced voltage stabilizing segment effectively improve the direct current resistance of the cable material. The high-voltage direct-current cable material prepared by the method is simple in preparation process and low in cost, and has excellent mechanical properties and electrical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing epoxy and DCP double-crosslinked EAA and LDPE cable materials, belonging to the technical field of high-voltage direct current cable material preparation. Background Art

[0002] With the rapid development of high-voltage commutation technology and high-power power electronic devices, countries around the world are paying more and more attention to the development of high-voltage direct current transmission technology. Compared with the AC transmission system, the DC transmission system has the advantages of large transmission capacity, long transmission distance, more flexible power regulation, and high system operation reliability. It is widely used in the fields of new energy grid connection, island power supply and long-distance cross-sea transmission. Among them, high-voltage direct current cable is the key equipment in high-voltage direct current transmission, and the insulation reliability of high-voltage direct current cable plays a major role in the stability of the high-voltage transmission network.

[0003] The breakdown characteristics of high-voltage DC cable materials are one of their key electrical characteristics. According to the breakdown field strength of the cable insulation material, the insulation characteristics and voltage resistance performance of the cable material can be evaluated. Generally speaking, the breakdown of cable materials is a one-way and irreversible process. After the cable material breaks down, it will leave irreversible channels such as holes and cracks, and its insulation characteristics will also be permanently damaged.

[0004] Cross-linked polyethylene has been widely used in the field of high-voltage DC cable materials due to its excellent electrical insulation properties. Researchers have conducted a lot of research on improving the performance of cross-linked polyethylene insulation materials. The main methods currently used are nano-doping modification, grafting modification and chemical modification. Nano-doping modification is the introduction of nano-sized fillers into the material through physical and chemical methods and surface modification to improve the electrical insulation properties of polyethylene materials; grafting modification is a modification method that uses free radical polymerization to introduce functional side groups on the polyolefin molecular chain; chemical modification is a type of modification method in which the polymer molecular chain undergoes a chemical reaction to change the atoms or atomic groups on the molecular chain.

[0005] The present invention utilizes the characteristics of cross-linked ethylene acrylic acid copolymer EAA, which has good insulation performance and excellent mechanical properties, adopts biphenyl type small molecule epoxy compound and DCP as double cross-linking agents, constructs XLPE and epoxy / EAA double cross-linking system, and at the same time introduces benzene ring and carbonyl group and other functional groups with voltage stabilizing effect into the system through small molecule epoxy compound, so that the DC breakdown characteristics of the cable material are significantly improved. Summary of the invention

[0006] Low-density polyethylene (LDPE) is widely used in the cable insulation material industry because of its good electrical insulation, processability, extensibility and relatively low cost. Ethylene acrylic acid copolymer (EAA) is a polymer compound formed by copolymerization of ethylene and acrylic acid. It has good adhesion, weather resistance and toughness and is widely used in packaging, adhesives and other fields. The present invention adopts two thermoplastic polymers (low-density polyethylene (LDPE) and ethylene acrylic acid copolymer (EAA) containing carboxyl monomers) as matrix resins, adopts a melt blending method, and adds biphenyl-type small molecule epoxy compounds and diisopropylbenzene peroxide (DCP) as double crosslinking agents. Under heating and pressure, DCP decomposes to cause LDPE to undergo a crosslinking reaction to form XLPE, and the epoxy group opens the ring and undergoes a crosslinking reaction with the carboxyl group in EAA to form a crosslinked EAA structure. The double crosslinking system merges with each other, and the crosslinked EAA effectively improves the mechanical strength of the material. At the same time, the epoxy / EAA crosslinking system introduces deep electron traps and voltage-stabilizing fragments, suppresses the accumulation of space charges, and greatly improves the DC breakdown characteristics of the cable material without the need for additional additives. In addition, since the epoxy / EAA cross-linking network improves the mechanical strength of the cable material, the amount of DCP is reduced compared to the common cross-linked polyethylene on the market, effectively preventing the occurrence of scorching and over-cross-linking.

[0007] The technical solution of the present invention:

[0008] One of the purposes of the present invention is to provide a method for preparing an epoxy and DCP double crosslinked EAA and LDPE cable material, characterized in that the crosslinking agent dicumyl peroxide DCP accounts for 1.6 parts by weight of low-density polyethylene, and the biphenyl type small molecule epoxy compound / EAA / LDPE blend material includes, by weight: 73.80 to 93.45 parts of low-density polyethylene LDPE, 5 to 20 parts of ethylene acrylic acid copolymer EAA, and 1.55 to 6.20 parts of epoxy compound.

[0009] It is further defined that EAA is an ethylene acrylic acid copolymer having an acrylic acid content of 6-8%.

[0010] It is further specified that the LDPE model is BASF-YPC 2220H.

[0011] It is further defined that the epoxy is 4,4'-biphenyl diglycidyl ether (BEB).

[0012] The second object of the present invention is to provide a method for preparing epoxy and DCP double cross-linked EAA and LDPE cable materials, the method comprising the following steps:

[0013] S1, melt blending: blend all raw materials evenly to obtain LDPE / EAA / DCP / BEB blended composite material;

[0014] S2, processing and molding: the LDPE / EAA / DCP / BEB blended composite material is pressed and molded in a flat vulcanizer, and then cross-linked under pressure, and then vacuum dried after cooling to obtain the LEDB high-voltage DC cable material.

[0015] It is further defined that S1 is specifically as follows: first, low-density polyethylene is added to a torque rheometer at 110°C and 60 rpm and kneaded for 5 minutes, then EAA and epoxy compound are added and kneaded for 7 minutes, and finally DCP is added and kneaded for no more than 3 minutes. After uniform mixing, LDPE / EAA / DCP / BEB blended material can be obtained.

[0016] It is further defined that the pressing temperature in S2 is 110° C. and the pressure is 15 MPa.

[0017] It is further defined that the pressure cross-linking temperature in S2 is 175° C. and the pressure is 15 MPa.

[0018] It is further defined that the vacuum drying treatment temperature in S2 is 80° C. and the time is 24 h.

[0019] A third object of the present invention is to provide an application of the above-mentioned cable material, specifically, the cable material is used to make a high-voltage direct current cable.

[0020] The present invention has the following beneficial effects:

[0021] (1) The present invention uses DCP and biphenyl-type small molecule epoxy compounds as dual cross-linking agents to construct a dual cross-linking system of XLPE and biphenyl-type small molecule epoxy / EAA, which greatly improves the DC breakdown characteristics of the cable material.

[0022] (2) The double cross-linked network constructed by the present invention can not only reduce the amount of cross-linking agent DCP while ensuring excellent mechanical properties and effectively prevent the occurrence of over-cross-linking, but also can introduce deep traps (carbonyl electron-deficient groups) and voltage-stabilizing fragments (biphenyl structures) in situ, without adding additional additives, to improve electric field distortion and enhance the electrical resistance of cable materials.

[0023] (3) The cable material LEDE prepared by the present invention has cheap and easily available raw materials, a simple production process, and good economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Comparative graphs of infrared spectrum test results of cable materials provided in different embodiments;

[0025] Figure 2 Thermal extension performance test diagram of cable materials provided for different embodiments;

[0026] Figure 3 A graph showing tensile test results of cable materials provided for different embodiments;

[0027] Figure 4 Weibull distribution diagram of DC breakdown field strength of cable materials provided in different embodiments, wherein a is an experimental group and b is a control group;

[0028] Figure 5 A comparison diagram of conductivity test curves of cable materials provided in different embodiments, wherein a is an experimental group and b is a control group. DETAILED DESCRIPTION

[0029] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0030] In the following examples, dicumyl peroxide (DCP) and epoxy compound 4,4'-biphenyl diglycidyl ether (BEB) were selected as crosslinking agents.

[0031] Embodiment 1:

[0032] The process of preparing LEDB cable material in this example is as follows:

[0033] (1) Melt blending: 37.38 g of LDPE was added into a torque rheometer and melted at 110 °C with a rotation speed of 60 r / min. After mixing for 5 min, 2 g of EAA and 0.62 g of 4,4'-biphenyl diglycidyl ether (BEB) were added and mixing continued for 7 min. Finally, 0.6 g of DCP was added and mixed for 3 min to obtain a blended composite material.

[0034] (2) Processing: The blended composite material was pressed in a flat vulcanizer at a temperature of 110°C and a pressure of 15 MPa, and then pressed for 30 min at a temperature of 175°C and a pressure of 15 MPa to complete crosslinking, thereby obtaining LE5D 1.6 B High voltage DC cable material.

[0035] Embodiment 2:

[0036] (1) Melt blending: 34.76 g of LDPE was added into a torque rheometer and melted at 110 °C with a rotation speed of 60 r / min. After mixing for 5 min, 4 g of EAA and 1.24 g of BEB were added and mixing was continued for 7 min. Finally, 0.56 g of DCP was added and mixed for 3 min to obtain a blended composite material.

[0037] (2) Processing: The blended composite material was pressed in a flat vulcanizer at a temperature of 110°C and a pressure of 15 MPa, and then pressed at a temperature of 175°C and a pressure of 15 MPa for 30 min to complete crosslinking and obtain LE 10 D 1.6 B High voltage DC cable material.

[0038] Embodiment 3:

[0039] (1) Melt blending: 32.14 g of LDPE was added into a torque rheometer and melted at 110 °C at a rotation speed of 60 r / min. After mixing for 5 min, 6 g of EAA and 1.86 g of BEB were added and mixing was continued for 7 min. Finally, 0.51 g of DCP was added and mixed for 3 min to obtain a blended composite material.

[0040] (2) Processing: The blended composite material was pressed in a flat vulcanizer at a temperature of 110°C and a pressure of 15 MPa, and then pressed at a temperature of 175°C and a pressure of 15 MPa for 30 min to complete crosslinking and obtain LE 15 D 1.6 B High voltage DC cable material.

[0041] Embodiment 4:

[0042] (1) Melt blending: 29.52 g of LDPE was added into a torque rheometer and melted at 110 °C at a speed of 60 r / min. After mixing for 5 min, 8 g of EAA and 2.48 g of BEB were added and mixing continued for 7 min. Finally, 0.47 g of DCP was added and mixed for 3 min to obtain a blended composite material.

[0043] (2) Processing: The blended composite material was pressed in a flat vulcanizer at a temperature of 110°C and a pressure of 15 MPa, and then pressed at a temperature of 175°C and a pressure of 15 MPa for 30 min to complete crosslinking and obtain LE 20 D 1.6 B High voltage DC cable material.

[0044] Embodiment 5:

[0045] (1) Melt blending: 34.76 g of LDPE was added into a torque rheometer and melted at 110°C with a rotation speed of 60 r / min. After mixing for 5 min, 4 g of EAA and 1.24 g of BEB were added and mixing was continued for 10 min to obtain a blended composite material.

[0046] (2) Processing: The blended composite material was pressed in a flat vulcanizer at a temperature of 110°C and a pressure of 15 MPa, and then pressed at a temperature of 175°C and a pressure of 15 MPa for 30 min to complete crosslinking and obtain LE 10 B High voltage DC cable material.

[0047] Embodiment 6:

[0048] (1) Melt blending: 36 g of LDPE was added into a torque rheometer and melted at 110 °C at a rotation speed of 60 r / min. After mixing for 5 min, 4 g of EAA was added and mixing was continued for 7 min. Finally, 0.58 g of DCP was added and mixed for 3 min to obtain a blended composite material.

[0049] (2) Processing: The blended composite material was pressed in a flat vulcanizer at a temperature of 110°C and a pressure of 15 MPa, and then pressed at a temperature of 175°C and a pressure of 15 MPa for 30 min to complete crosslinking and obtain LE 10 D 1.6 High voltage DC cable materials.

[0050] Embodiment 7:

[0051] (1) Melt blending: 36 g of LDPE was added into a torque rheometer, melted at 110 °C, with a rotation speed of 60 r / min, and mixed for 5 min. Then, 4 g of EAA was added and mixed for 10 min to obtain a blended composite material.

[0052] (2) Processing and molding: The blended composite material is pressed in a flat vulcanizer at a temperature of 110°C and a pressure of 15 MPa to obtain LE 10 High voltage DC cable materials.

[0053] Effect example:

[0054] The performance tests were conducted on the LEDB high voltage DC cable materials with different formula ratios prepared in the above-mentioned Examples 1 to 4. The specific test process and results are as follows:

[0055] (1) The molecular structure of the above cable materials was tested, analyzed and characterized by Fourier transform infrared spectrometer (FT / IR-6100) to verify whether the epoxy compound BEB successfully participated in the cross-linking reaction.

[0056] Depend on Figure 1 It can be seen that compared with LE and LED cable materials, LEDB cable materials have a -1 A new absorption peak appears at 1705cm, which corresponds to the characteristic absorption peak of hydroxyl groups generated in the cable material after the epoxy compound is cross-linked with EAA. -1The peak red-shifted to 1730 cm -1 , and turned into a broad peak, which corresponds to the characteristic peak of the carboxyl group in the cable material being converted into an ester group after the epoxy compound and EAA are cross-linked. This shows that the epoxy compound BEB successfully reacted with the carboxylic acid monomer in EAA, and the cross-linking reaction was successful.

[0057] (2) The above cable materials were tested by RYS-Ⅲ thermal elongation tester according to the national standard GB / T2951.21-2008. The test chamber test temperature was set to 200℃. After the sample was placed in the test chamber for 15 minutes, the distance between the two marked lines was observed through the observation window, and the distance was measured and the thermal elongation of the sample was calculated. Each material was tested 3 times and the average value was taken. The results are as follows: Figure 2 shown.

[0058] According to GB / T12527-2008, the thermal elongation of XLPE insulated cables under load should not exceed 175%. Figure 2 It can be seen that the thermal elongation of LEDB cable materials meets the test standard requirements, and the degree of cross-linking achieved has met the use standard of cross-linked polyethylene. With the increase of EAA content, the thermal elongation of cable materials tends to decrease. This is because the performance of cable materials in withstanding external stress at high temperature will become better with the increase of EAA / BEB cross-linking network. When the EAA content is 20%, the thermal elongation can reach 62.5%.

[0059] (3) The above cable materials were tested by SUNS UTM2203 universal testing machine according to the national standard GB / T528-2009. According to the test method required by the standard, the above LEDB cable material samples were cut into dumbbell-shaped samples with a thickness of 1 mm using a cutter, with a total length of 75 mm and an effective test portion width of 4±0.2 mm. The surface was smooth and free of defects visible to the naked eye, and a marker pen was used to mark the narrow section with a marking line of 20 mm spacing. The clamp spacing was set to 20 mm, the tensile rate was set to 250 mm / min, and each material was tested 5 times.

[0060] According to the requirements of standard GB / T22078.1-2008, the tensile strength and elongation at break of XLPE materials for high-voltage cables should be no less than 12.5MPa and 200% respectively. Figure 3 It can be seen that under the same experimental conditions, as the amount of EAA / BEB increases, the mechanical properties of LEDB cable materials show a trend of first increasing and then decreasing. 10 D 1.6 Cable material B has the best mechanical properties, with an elongation at break of 1070.3% and a tensile strength of 27.3MPa. The elongation at break is 5.35 times higher than the standard, and the tensile strength is 2.18 times higher than the standard.

[0061] (4) The above cable materials were subjected to DC breakdown field strength tests at room temperature using cylindrical electrodes, with a voltage step-up rate of 1 kV / s and a sample thickness of 50 um. The samples and electrodes were in transformer oil throughout the entire process. Fifteen groups of samples were selected for repeated experiments under each experimental condition, and 10 groups of valid data were selected.

[0062] The Weibull distribution of the DC breakdown strength of the above cable materials is as follows: Figure 4 shown.

[0063] Depend on Figure 4 It can be seen that with the increase of BEB / EAA, the DC breakdown field strength first increases and then decreases. 10 D 1.6 B high voltage DC cable material has the highest DC characteristic breakdown strength, reaching a maximum value of 453.6kV / mm, compared with the blank test LDPE, LE 10 LE 10 B.LE 10 D 1.6 The four cable materials increased by 46.65%, 34.36%, 20.10% and 18.34% respectively. The LEDB cable material at this content has excellent DC breakdown characteristics.

[0064] (5) According to the electric field strength and temperature of the insulation layer of the high-voltage DC cable during operation, the above cable material is subjected to a conductance current test on a 200um sample at a field strength of 5kV-40kV at room temperature to obtain its E-σ curve, as shown in FIG. Figure 3 As shown, the polarization time was set to 2 h.

[0065] Depend on Figure 5 It can be seen that under the same experimental conditions, the conductivity of LEDB high voltage DC cable materials is significantly lower than that of LDPE, which is similar to the DC breakdown test results. 10 D 1.6 The conductivity of cable material B is the lowest, and its conductivity at 20KV / mm is only 2.14×10 -12 S / m, which is only 1.1% of the conductivity of pure LDPE. This shows that the construction of the double cross-linked network interpenetrating structure and the introduction of functional groups effectively inhibit the accumulation of space charges inside the material, which greatly improves the DC electrical resistance of LEDB cable materials compared with traditional cross-linked polyethylene.

[0066] The above description is only a preferred embodiment of the present invention. In view of the fact that technicians in the field of the present invention can make appropriate changes and modifications to the above implementation mode, the present invention is not limited to the specific implementation mode described above. Some modifications and changes to the present invention should also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing epoxy and DCP double cross-linked EAA and LDPE cable materials, characterized in that The preparation method is as follows: a certain amount of low-density polyethylene LDPE and ethylene acrylic acid copolymer EAA, a small molecule biphenyl epoxy compound (BEB) and diisopropylbenzene peroxide (DCP) are added into a torque rheometer for melt blending to obtain a LDPE / EAA / DCP / biphenyl small molecule epoxy compound blended material; the blended material is pressed and formed in a flat vulcanizer, heated and cross-linked, and after cooling, a high-voltage DC cable material LEDB with significantly improved breakdown strength can be obtained.

2. The method for preparing an epoxy and DCP double cross-linked EAA and LDPE cable material according to claim 1, characterized in that The cross-linking agent is biphenyl type small molecule epoxy compound 4,4'-biphenyl diphenol diglycidyl ether and dicumyl peroxide DCP.

3. The method for preparing an epoxy and DCP double cross-linked EAA and LDPE cable material according to claim 1, characterized in that The mass fraction of EAA is 5%-20% of the total mass of LDPE, EAA and 4,4'-biphenyl diglycidyl ether.

4. The method for preparing an epoxy and DCP double cross-linked EAA and LDPE cable material according to claim 1, characterized in that The mass fraction of the LDPE is 73.80-93.45% of the total mass of LDPE, EAA and 4,4'-biphenyl diglycidyl ether.

5. The method for preparing an epoxy and DCP double cross-linked EAA and LDPE cable material according to claim 1, characterized in that The mass fraction of the 4,4'-biphenyl diglycidyl ether is 1.55%-6.20% of the total mass of LDPE, EAA and 4,4'-biphenyl diglycidyl ether.

6. The method for preparing an epoxy and DCP double cross-linked EAA and LDPE cable material according to claim 1, characterized in that The amount of the cross-linking agent DCP is 1.6% of the mass fraction of LDPE.

7. The method for preparing an epoxy and DCP double cross-linked EAA and LDPE cable material according to claim 1, characterized in that Mainly used in high voltage DC cable materials.

8. The use according to claim 8, characterized in that The DC breakdown strength of the prepared high-voltage DC cable material can reach 453.6 kV / mm.

Citation Information

Patent Citations

  • Crosslinked polyethylene with repeatable processability and preparation method thereof

    CN115322406A

  • Preparation and application of epoxy cross-linked LLDPE / EAA composite insulating material

    CN117362693A

  • Peroxide cross-linked polyvinyl cable insulating material and preparation method thereof

    CN117720780A

  • Cable Comprising Crosslinked Layer Obtained From Polymer Composition

    US20190371489A1

Cited By

  • Composite cable insulation material doped with modified silicon dioxide and preparation method thereof

    CN121021963A

  • Composite cable insulating material doped with modified silica and preparation method thereof

    CN121021963B